2018
DOI: 10.1002/ajhb.23126
|View full text |Cite
|
Sign up to set email alerts
|

The association of irregular sleep habits with the risk of being overweight/obese in a sample of Portuguese children aged 6–9 years

Abstract: Findings revealed that shorter and longer than recommended sleep duration was positively associated with risk of obesity in boys on weekdays. Furthermore, pediatric obesity risk could be highly influenced by the education level of fathers of both males and females. Future research should extend a similar design, using objective measures of sleep duration to confirm some of the afore-mentioned results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In Portuguese school-age children, findings about abdominal obesity and detailed anthropometric measures among children with immigrant background (and natives) are rare. In 2013-2014, Rodrigues et al [38] found a prevalence of 21.9% and Albuquerque et al [39] found 23.6% in central region of Portugal. Both studies presented higher values compared with our study.…”
Section: Discussionmentioning
confidence: 99%
“…In Portuguese school-age children, findings about abdominal obesity and detailed anthropometric measures among children with immigrant background (and natives) are rare. In 2013-2014, Rodrigues et al [38] found a prevalence of 21.9% and Albuquerque et al [39] found 23.6% in central region of Portugal. Both studies presented higher values compared with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' education was used as a proxy for SES. It has been previously done in the Portuguese context (Machado-Rodrigues et al, 2018) given that education has been positively associated with more health-related knowledge and a higher capacity to put it into practice (Ball & Crawford, 2006). The parental education was scored based upon the Portuguese Education system and categorized in three levels: low (9 years of completed schooling or less), medium (secondary educational level; 10-12 years), and high (university degree).…”
Section: Methodsmentioning
confidence: 99%
“…The present study is part of the “Inequalities in Childhood Obesity: the impact of the socioeconomic crisis in Portugal from 2009 to 2015” project. Sampling procedures were the same as those followed in a previous project conducted during 2009 to 2010 to assess childhood obesity prevalence and determinants (Jago et al, 2012; Machado‐Rodrigues, Fernandes, Gama et al, 2018). In brief, the sampling procedure for the 2009 to 2010 cross‐sectional study was based on a stratified random design that accounted for the number of children by age and sex in each district, to provide a nationally representative survey of children aged 3 to 10 years.…”
Section: Methodsmentioning
confidence: 99%